Post-incarceration outcomes for individuals who continued methadone treatment while in Connecticut jails, 2014–2018. (1st October 2021) - Haas, Alissa; Viera, Adam; Doernberg, Molly; Barbour, Russell; Tong, Guangyu; Grau, Lauretta E.; Heimer, Robert
Highlights: A pilot program provided methadone to jailed individuals who had been receiving methadone prior to being incarcerated. Treatment while in jail significantly increased the likelihood and rate of resumption of treatment post-release. Treatment while in jail significantly decreased post-release non-fatal opioid overdoses. Treatment while in jail had no discernable effect on the rate of reincarceration. Abstract: Purpose: To assess post-release outcomes associated with continuation of methadone treatment in correctional centers. Methods: This case-control study of the post-incarceration impact of pilot methadone programs operating in jails in New Haven and Bridgeport, Connecticut, USA was conducted in 2014−18. The study compared non-fatal overdose, fatal overdose, reincarceration, and resumption of methadone in the community experienced by 1564 eligible men, 660 (42.2 %) of whom continued treatment while incarcerated. Results: Continuation of methadone was associated with a significant decrease in non-fatal overdose (OR:0.55; 95 % CI: 0.36, 0.85) and a greater likelihood of resuming methadone treatment in the community post-release (OR:2.56; 95 % CI: 2.07, 3.16). Time to resumption of methadone was shortened by treatment while time to non-fatal overdose was increased. Treatment while incarcerated resulted in a modest but not significant decrease in fatal overdoses and no difference in reincarceration between those who did and did not receive methadone. However, resumption of methadone after release did significantly reduce fatal overdoses (OR = 0.26, 95 % CI: 0.11, 0.62, p = 0.002). Conclusion and relevance: Improvements in post-release outcomes of non-fatal overdose and treatment reengagement emphasize the benefits of continuing medication-based treatment for opioid use disorder within the criminal justice system for those receiving it prior to being incarcerated.